Xamanismo ártico na Escandinávia: uma análise comparada da ocorrência de fenômenos xamânicos entre os povos nórdicos, balto-fínicos e sámis - Alves, Victor Hugo Sampaio (2023)
M anifestations of magic in the cultural contexto of Scandinavia have a long tradition in the academic debate. The focus almost always falls upon the Norsemen, mainly due to the fact that their religious and mythological traditions were considerably more doc umented than the ones about their Saami or Balto F innic neighbours. One of the greatest discussions is in regards to whether the magic expressios of the Norse are of shamanic nature or not and, if the case is positive, to ponder if it would have occured as an inheritance of an Indo European shamanism or as a result of influences from Arctic shamanism, brought from Siberia by Finno Ugric peoples such as the Saami and the Balto Finnic. The presente thesis holds to the hypothesis that the religions of the Nors emen could be seen as a cultural branch of the Arctic shamanism, and that there would have occured, in the Scandinavian region, a considerable traffic of elements, structures, symbols, performances and rituals tipically shamanic, which were all shared by t hese three peoples. In order demonstrate this argument we are going to analyze the literary sources available about the magical practices, the religion and mythology of each one of these peoples, highligthing a number of ritualistic, performatic, mythologi cal and ideological resemblances which are known traces of Arctic shamanism. We also highlight the occurence of many deities, in the mythological corpus, who bear many shamanic traits and that could therefore have been perceived as cultural models for the ritual specialists of the region who operated with a shamanic repertoire.